(untitled) (CIPEEX, 2025)
This study analyzes the impacts of digital disinformation on the Brazilian Electoral process, with emphasis on the phenomenon of fake news and the increasing use of technologies such as algorithms, bots, and artificial Intelligence in Campaigns. The main objective is to examine how the circulation of false content undermines Electoral integrity, compromisses equality among candidates, and threatens fundamental democratic principles such as morality, fairness, and truthfulness. The methodology adopted was qualitative, combining bibliographic research from national and international literature published between 2018 and 2025 with a normative analysis of Brazilian legislation, particularly the Electoral Code and Resolution No. 23,732/2024 of the Superior Electoral Court (TSE). The results demonstrate that digital disinformation significantly interferes with voters’ freedom of choice, distorts political decision-making, and weakens trust in institutions. Moreover, the current business model of social media platforms, centered on engagement and virality, facilitates the large-scale dissemination of false information. Although Brazil has already established legal mechanisms to address electoral disinformation, and the TSE has advanced in regulation, repression alone proves insufficient. The conclusion emphasizes the need for preventive strategies, highlighting media literacy and digital education as essential tools to strengthen citizens’ critical capacity and safeguard the Democratic Rule of Law. International experiences, such as the European Union’s Digital Services Act, provide valuable referencies to improve Brazilian regulation. Therefore, confronting Electoral disinformation must be understood as a continuous and collective effort involving the State, civil Society, and technology companies to ensure Transparency, legitimacy, and trust in the democratic process.